2012
DOI: 10.1016/j.photonics.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Compact optical circulator based on a uniformly magnetized ring cavity

Abstract: We propose a new class of compact integrated optical circulators providing a large isolation level while maintaining a straightforward technological feasibility. Their layout is based on a nonreciprocal radial Bragg cavity composed of concentric magneto-optical rings. The circulator ports are standard rib waveguides, butt-coupled to the cavity by cutting through its outer rings. The device is specifically designed for operation in a uniform external magnetic field. Using a coupled-mode description of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…It was reported that with increasing the amount of Bi substitution for rare-earth element, FR of Bi:RIG becomes large [2]. Bi:RIG have been used for magneto-optical device elements in such as magnetoplasmonic structure [3,4], optical isolators [5], circulators [6], and magnet photonic crystals (MPCs) used in magneto-optic spatial light modulators (MOSLMs) [7]. Among them, bismuth substituted gadolinium iron garnet (Bi:GdIG) is one of the ferrimagnetic rate-earth iron garnets showing perpendicular magnetic anisotropy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that with increasing the amount of Bi substitution for rare-earth element, FR of Bi:RIG becomes large [2]. Bi:RIG have been used for magneto-optical device elements in such as magnetoplasmonic structure [3,4], optical isolators [5], circulators [6], and magnet photonic crystals (MPCs) used in magneto-optic spatial light modulators (MOSLMs) [7]. Among them, bismuth substituted gadolinium iron garnet (Bi:GdIG) is one of the ferrimagnetic rate-earth iron garnets showing perpendicular magnetic anisotropy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Bi-substituted rare-earth iron garnets have long been known and received much attention because of their high magneto optical effects (high transparency and large Faraday rotation in near infrared region 1) which made these materials very attractive among all semi-transparent dielectrics for various fundamental investigations as well as practically usable materials for magneto-optical device elements such as optical isolators 2) , circulators 3,4) , printers 5) and MPC which is used in magneto-optic spatial light modulators (MOSLM) 6,7,8,9) . A single crystal garnet with perpendicular magnetic anisotropy and two polarizers have been used as a pixel element to switch the optical output depending on the up and down magnetization owing to Faraday effect in MOSLMs.…”
Section: Introductionmentioning
confidence: 99%
“…A further reduction in size can be achieved by a resonance enhancement of the interaction between light wave and the magneto-optical active medium. There are concepts for four-port circulators using ring resonators coupled to two waveguides [4,5] and there are concepts for three-port circulators using photonic-crystal resonators [6][7][8][9]. For both concepts the footprint is comparable and is in the 10 μm range.…”
mentioning
confidence: 99%
“…But there are no realistic 3D concepts proposed for photonic-crystal isolators so far. The vertical confinement in the photonic-crystal slab will in most cases not be achieved with the two-dimensional (2D) structures discussed in [6][7][8][9]. Magneto-optical ring resonators, on the other hand, have already been shown experimentally by bonding a garnet to a silicon-ring resonator [10] and by deposition of a garnet on a silicon ring with pulsed laser deposition [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation